The Rhetoric of the New Testament : A Bibliographic Survey - Watson, Duane F., (Tools for Biblical Study, 2006)
A new, comprehensive bibliography of books and articles on the rhetoric of the New Testament published since AD 1500. The bibliography is arranged by categories, which include Jewish heritage, invention, arrangement, style, hermeneutics, with specific listings for each book of the NT. It is prefaced with a select bibliography of primary and secondary sources on classical and modern rhetoric. An invaluable research tool.